Effect of conventional and alternative products on postharvest disease control in avocados - Fischer, Ivan Herman; Moraes, Matheus Froes de; Arruda Palharini, Maria Cecilia de; Fileti, Mirian de Souza; Sodario Cruz, Juliana Cristina; Firmino, Ana Carolina [UNESP] (Soc Brasileira Fruticultura, 2018)
Postharvest diseases constitute a serious problem for avocado commercialization. Thus, the present study aimed to evaluate the effect of conventional and alternative products in controlling diseases affecting 'Hass' avocados in the field and in the postharvest by carrying out physicochemical characterization of fruits subjected to postharvest treatments. In the field, besides the management adopted by the farmer, seven products were sprayed three times during fruiting for evaluation. Postharvest products were diluted in water or in oxidized polyethylene wax and shellac. Water treatments with potassium phosphite, Soil-Set (R), chlorine dioxide, thyme essential oil, sodium bicarbonate, lemon grass essential oil and thiabendazole reduced the incidence of diseased fruits, and anthracnose, the main disease, was controlled with sodium bicarbonate, lemon grass essential oil and thiabendazole. Greater soluble solids content was found for control (water), chlorine dioxide, acibenzolar-S-methyl and thiabendazole. For the products that reduced anthracnose, there was no correlation between the disease and the physicochemical parameters, evidencing that the disease control is not associated with delayed ripening. For wax treatments, diseases were not controlled, and the fruits presented lower titratable acidity with thyme essential oil, sodium bicarbonate, control (wax), acibenzolar-S-methyl and lemon grass essential oil. Control and thyme essential oil were highlighted for maintaining the green coloration of the fruit skin for the shortest period. Under field conditions, azoxystrobin, thiabendazole, difenoconazole+azoxystrobin and acibenzolar-S-methyl+azoxystrobin reduced the occurrence of diseased fruits, while anthracnose control was only obtained with azoxystrobin.
Keywords: Rot; Persea americana; Colletotrichum; control disease